Stereotactic Radiation Therapy (SRT) for Brain Metastases of Multiple Primary Tumors: A Single Institution Retrospective Analysis - Gu, Lei; Qing, Shuiwang; Zhu, Xiaofei; Ju, Xiaoping; Cao, Yangsen; Jia, Zhen; Shen, Yuxin; Cao, Fei; Fang, Fang; Zhang, Huojun (Frontiers in Oncology, 2019)
Purpose: To evaluate the efficiency and side effects of stereotactic radiation therapy (SRT) with or without other treatments for brain metastases (BM) from various primary tumors. Methods: This was a retrospective analysis of 161 patients with brain metastases treated with SRT. Clinical data, EGFR mutation status and survival data were collected. Follow-up data was analyzed until December 2018. Kaplan-Meier and Cox proportional hazards regression analyses were used for the survival analysis. Results: The median overall survival (OS) was 19 months. No difference was observed in OS between SRT group and SRT + whole brain radiation therapy (WBRT) groups (p = 0.717). Statistically significant factors of better OS after univariable analysis were no extracranial metastases(p = 0.016), BED10≥50Gy(p = 0.049), oligometastases(1-3 brain metastases) (p＜0.001), GPA score≥2.5(p = 0.003), RPA class I(p = 0.026), NSCLC tumor type(p = 0.006), targeted therapy(p＜0.001) and controlled extracranial disease(p = 0.011). Multivariate analysis indicated that higher BED10(≥50Gy, HR=0.504, p = 0.027), controlled extracranial disease (HR=0.658, p = 0.039) and targeted therapy (HR=0.157,＜0.001) were independent favorable predictors for OS. Besides that, we also find that the median overall survival (OS) was 22 months in NSCLC patients and controlled extracranial disease (HR=0.512, p = 0.012) and targeted therapy (HR=0.168,＜0.001) were independent favorable predictors for OS. Conclusion: For patients with brain metastases, stable extracranial disease, higher BED10 (≥50Gy) and targeted therapy may predict a favorable prognosis.